2003
DOI: 10.1164/rccm.200210-1167oc
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol Delivery and Modern Mechanical Ventilation

Abstract: Aerosol delivery via a mechanical ventilator remains unregulated with no standards for drug delivery to intubated patients. Bench models predicting drug delivery have not been validated in vivo. For modern ventilator designs, we chose to identify, on the bench, the most important variables affecting aerosol delivery and to correlate in vitro predictions of aerosol delivery with in vivo end points independent of patient response. Test aerosols of albuterol and antibiotics were compared. Bench measurements of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
174
2
7

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(187 citation statements)
references
References 12 publications
4
174
2
7
Order By: Relevance
“…As compared with previous devices used to aerosolize PFC (12,15), this system bypasses the oropharynx, avoiding the high deposition that tends to occur within the endotracheal tube (18). Therefore, particles >5 µm can reach the lungs and have a therapeutic effect (14).…”
Section: Discussionmentioning
confidence: 99%
“…As compared with previous devices used to aerosolize PFC (12,15), this system bypasses the oropharynx, avoiding the high deposition that tends to occur within the endotracheal tube (18). Therefore, particles >5 µm can reach the lungs and have a therapeutic effect (14).…”
Section: Discussionmentioning
confidence: 99%
“…Humidifi cation of the ventilator circuit is one of the factors that were well studied for optimization of aerosol delivery in NIV patients [5][6][7][8][9][10][11]. Optimal humidifi cation of the inhaled gas could improve patient comfort, facilitate use of the mask, and improve bronchodilator effects in those requiring NIV [2].…”
Section: Introductionmentioning
confidence: 99%
“…Most studies of humidifi cation effects on aerosol delivery were in-vitro and all of them recommend switching off the humidifi er while delivering aerosol to NIV patients for better delivery [5][6][7][8][9][10][11]. However, the undesirable effect of inhaled dry gas, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…1,2,[4][5][6] Aerosol delivery varies with different types of aerosol generators, brands of nebulizer used, and their position in the ventilator circuit. [6][7][8] Other authors reported that the higher the peak inspiratory flow, the greater the impact of inspiratory waveform on aerosol delivery.…”
Section: Introductionmentioning
confidence: 99%
“…1,2,[4][5][6] Aerosol delivery varies with different types of aerosol generators, brands of nebulizer used, and their position in the ventilator circuit. [6][7][8] Other authors reported that the higher the peak inspiratory flow, the greater the impact of inspiratory waveform on aerosol delivery. 5 Furthermore, factors improving aerosol delivery through mechanical ventilation in pediatric patients include larger endotracheal tubes (ETTs), use of metered-dose inhalers with spacers, synchronization with inspiration, use of heliox (80:20 helium-oxygen mixture) as a gas power source, and positioning a jet nebulizer distal to the ventilator circuit.…”
Section: Introductionmentioning
confidence: 99%